2008
DOI: 10.1001/archoto.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Core Needle Biopsy

Abstract: For lesions that require immunohistochemical staining or that remain undiagnosed after fine-needle aspiration, use of core needle biopsy should be considered before excisional biopsy. Core needle biopsy is a safe, effective, time-efficient, inexpensive procedure that can be an important tool for diagnosing head and neck masses, especially when lymphoma is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Large-gauge needles generally provide greater diagnostic value as pathologists can more readily determine the specific histological type of mass lesions from the larger tissue core; however the risk of hemorrhage may increase (15). An 18 gauge biopsy needle is widely accepted to be effective and safe in biopsies of the head and neck areas (1, 2), but no previous study has contrasted its use against 20 gauge needles. Our results showed that either an 18 or a 20 gauge biopsy needle yields similar diagnostic outcomes in the biopsy of head and neck lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-gauge needles generally provide greater diagnostic value as pathologists can more readily determine the specific histological type of mass lesions from the larger tissue core; however the risk of hemorrhage may increase (15). An 18 gauge biopsy needle is widely accepted to be effective and safe in biopsies of the head and neck areas (1, 2), but no previous study has contrasted its use against 20 gauge needles. Our results showed that either an 18 or a 20 gauge biopsy needle yields similar diagnostic outcomes in the biopsy of head and neck lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical open biopsy is commonly used to achieve the diagnosis, but it is invasive and has notable risks. Ultrasound (US) guidance has been generally advocated for the biopsy of most head and neck lesions, especially for the superficial areas (2). However, this technique has limited utility for lesions in the deep suprahyoid region because the underlying intervening osseous and air-containing structures may contribute to a limited ultrasound window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the accuracy of CNB depends on several factors, such as the operators' skills and experience. However, inherent nodule characteristics can be more important factors in inducing unsatisfactory sampling under US guidance, compared to operator factors (3031). In this study, we included 140 thyroid nodules with relatively similar characteristics of K-TIRADS category 3 or 4.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical biopsy of these lesions can be challenging with notable risk. Generally, ultrasound (uS)-guided needle biopsy is effective for superficial head and neck lesions 1,2 . however, there is a limited acoustic window for visualization of the deeper head and neck area due to intervening osseous and air-containing structures 3 .…”
Section: Introductionmentioning
confidence: 99%